Syntactic analysis on the consistency of Jokowi's rhetorical strategy as president and presidential candidate - Rachmat Kriyantono (Politeknik Negeri Bali, 2019)
This study aims to describe President Jokowi's rhetorical strategies during the 2019 campaign on Instagram and its consistency with the rhetorical strategy as president. Rhetoric is not just a speech strategy, not a speech that tends to lie to manipulate or control people, and not talk much without action. Because of political competition, it can be concluded that the use of words and sentences (syntax) as rhetorical strategies also compete in building a positive image. Syntactic analysis was conducted to describe the categories of use of words and sentences as a rhetorical strategy to build a positive image. The method used was content analysis of 508 Instagram posts during the campaign period. Social media is a new innovation in spreading messages of rhetoric in the form of words and sentences more quickly and easily accessing them. The interview method was also conducted on President Jokowi's communication team to find out how these rhetorical strategies were carried out in order to proof the consistency between rhetorical strategies during campaigns and rhetorical strategies as a President. The results of this study confirm that not all rhetorical strategies are used, but, only the use of positive rhetorics to build positive image. Syntactic analysis shows that Jokowi-Amin does not use negative words and sentences. Not all rhetorical strategies for building imagery are displayed on Instagram, namely @ jokowi.amin does not use intimidation and self-depreciation strategies. The interviews also display that the rhetoric strategies during campains are consistent with the president’s strategies.